Letting Go of the Dream of Traffickers behind Bars: We can do better for exploited workers - Rende Taylor, Lisa (Anti-Trafficking Review, 2020)
Response to the ATR debate proposition ‘It is worth undermining the anti-trafficking cause in order to more directly challenge the systems producing everyday abuses within the global economy.’